2021
DOI: 10.3389/fpsyg.2021.703678
|View full text |Cite
|
Sign up to set email alerts
|

Chief Executive Officer Proactive Personality and Acquisitions: A Fuzzy Set Qualitative Comparative Analysis of China's Listed Firms

Abstract: The role of the CEO in an enterprise's management decisions renders their individual characteristics influential in decisions about mergers and acquisitions (M&As). Personal characteristics are based on many aspects, therefore, we provide a multi-angle insight into the personal characteristics of managers. Drawing on the upper echelons theory, we examine whether CEOs' proactive personality affects merger and acquisition decisions. The fuzzy-set qualitative comparative analysis (fsQCA) is performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Individuals using their proactive trait as a resource to confront demanding situations were shown to mitigate the negative effects of ICT-enabled technostress like communication overload (Sumiyana & Sriwidharmanely, 2020). Although the application of fsQCA in micro-focused proactive personality literature is limited, studies have found that configurations containing the presence of this trait in CEO's and entrepreneurs influence strategic outcomes (e.g., Denoo & Soh, 2018;Yang, Bai, & Yang, 2021).…”
Section: Proactive Personality As a Resourcementioning
confidence: 99%
“…Individuals using their proactive trait as a resource to confront demanding situations were shown to mitigate the negative effects of ICT-enabled technostress like communication overload (Sumiyana & Sriwidharmanely, 2020). Although the application of fsQCA in micro-focused proactive personality literature is limited, studies have found that configurations containing the presence of this trait in CEO's and entrepreneurs influence strategic outcomes (e.g., Denoo & Soh, 2018;Yang, Bai, & Yang, 2021).…”
Section: Proactive Personality As a Resourcementioning
confidence: 99%